Energy at Origins: Favorable Thermodynamics of Biosynthetic Reactions in the Last Universal Common Ancestor (LUCA) - Wimmer, Jessica L. E.; Xavier, Joana C.; Vieira, Andrey d. N.; Pereira, Delfina P. H.; Leidner, Jacqueline; Sousa, Filipa L.; Kleinermanns, Karl; Preiner, Martina; Martin, William F. (Frontiers in Microbiology, 2021)
Though all theories for the origin of life require a source of energy to promote primordial chemical reactions, the nature of energy that drove the emergence of metabolism at origins is still debated. We reasoned that evidence for the nature of energy at origins should be preserved in the biochemical reactions of life itself, whereby changes in free energy, G, which determine whether a reaction can go forward or not, should help specify the source. By calculating values of G across the conserved and universal core of 402 individual reactions that synthesize amino acids, nucleotides and cofactors from H2, CO2, NH3, H2S and phosphate in modern cells, we find that 97 % of these reactions are exergonic (G ≤ 0 kJ·mol–1) at pH 7−10 and 80−100 °C under nonequilibrium conditions with H2 replacing biochemical reductants. While 23 % of the core's reactions involve ATP hydrolysis, 77 % are ATP independent, thermodynamically driven by G of reactions involving carbon bonds. We identified 174 reactions that are exergonic by –20 to –300 kJ·mol–1 at pH 9 and 80 °C and that fall into ten reaction types: six pterin dependent alkyl or acyl transfers, ten S-adenosylmethionine dependent alkyl transfers, four acyl phosphate hydrolyses, 14 thioester hydrolyses, 30 decarboxylations, 35 ring closure reactions, 31 aromatic ring formations and 44 carbon reductions by reduced nicotinamide, flavins, ferredoxin or formate. The 402 reactions of the biosynthetic core trace to the last universal common ancestor, LUCA, and reveal that synthesis of LUCA's chemical constituents required no external energy inputs such as electric discharge, UV-light or phosphide minerals. The biosynthetic reactions of LUCA uncover a natural thermodynamic tendency of metabolism to unfold from energy released by reactions of H2, CO2, NH3, H2S and phosphate.